Out of Sight: Social Control and the Regulation of Public Space in Manchester - Christopher J. Moss; Kate Moss (Social Sciences, 2019)
This paper considers the history and context of the control of public spaces, how this is regulated currently and how it relates to the politics of homelessness and community governance with a specific focus on the regulation of public space in the contemporary city of Manchester.